A poxvirus ankyrin protein LSDV012 inhibits IFIT1 in a host-species-specific manner by compromising its RNA binding ability - Xie, Shijie; Fang, Yongxiang; Liao, Zhiyi; Cui, Lianxin; Niu, Kang; Ren, Shuning; Zhu, Junda; Wu, Wenxue; Jing, Zhizhong; Peng, Chen (PLoS pathogens, 2025)
Poxviruses are large DNA viruses with an arsenal of immune-modulatory genes, many of which remain uncharacterized. Proteins with ankyrin repeats are distinct features of poxviruses, although the biological functions of ankyrin proteins are not fully understood. Lumpy skin disease virus (LSDV) encodes five proteins with ankyrin repeats. Here, we reveal the role of LSDV012, an ankyrin protein, in conferring resistance to type I interferon (IFN) in cells. Deletion of LSDV012 from LSDV significantly impacted viral replication in the presence of type I IFN, highlighting the importance of LSDV012 in antagonizing type I IFN responses. Further investigation revealed that LSDV012 interacted with interferon-induced proteins with tetratricopeptide repeats (IFITs), particularly IFIT1, altering its subcellular localization, interacting with its C-terminus and inhibiting its RNA-binding ability without inducing its degradation. Phylogenetic analysis demonstrated that LSDV012 orthologs are conserved in capripoxviruses and cervidpoxviruses , and exhibit host species-specific interactions with IFIT1. Notably, LSDV012 was able to rescue the degradation of IFIT1 mediated by VACV C9. These findings provide novel insights into the viral strategies employed by LSDV to subvert host antiviral defenses and underscore the evolutionary adaptations of poxvirus ankyrin proteins in host species-specific immune evasion.